Encapsulation of aluminium in geopolymers produced from metakaolin - Kuenzel, C.; Neville, T. P.; Omakowski, T.; Vandeperre, Luc; Boccaccini, Aldo R.; Bensted, J.; Simons, S. J. R.; Cheeseman, C. R. (Journal of Nuclear Materials, 2014)
Magnox swarf contaminated with trace levels of Al metal is an important UK legacy waste originated from the fuel rod cladding system used in Magnox nuclear power stations. Composite cements made from Portland cement and blast furnace slag form a potential encapsulation matrix. However the high pH of this system causes the Al metal to corrode causing durability issues. Geopolymers derived from metakaolin are being investigated as an alternative encapsulation matrix for Magnox swarf waste and the corrosion kinetics and surface interactions of Al with metakaolin geopolymer are reported in this paper. It is shown that the pH of the geopolymer paste can be controlled by the selection of metakaolin and the sodium silicate solution used to form the geopolymer. A decrease in pH of the activation solution reduces corrosion of the Al metal and increases the stability of bayerite and gibbsite layers formed on the Al surface. The bayerite and gibbsite act as a passivation layer which inhibits further corrosion and mitigates H generation. The research shows that optimised metakaolin geopolymers have potential to be used to encapsulate legacy Magnox swarf wastes. © 2014 Published by Elsevier B.V.